2014
DOI: 10.1002/pmh.1271
|View full text |Cite
|
Sign up to set email alerts
|

Lasting personality pathology following exposure to catastrophic trauma in adults: Systematic review

Abstract: A minority of adults who are exposed to severe trauma appear to go on to develop significant personality pathology. The observed personality disturbance is multifarious and more extensive than the prototype described in ICD-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…In other words, it is possible that IPDE caseness observed in some participants in the study has emerged secondary to severe trauma. This would be consistent with the findings from a recent systematic review which suggested that a proportion of adults with no pre-trauma personality pathology appear to go on to develop significant personality problems following the exposure to severe trauma [16]. However, one would need to demonstrate that severe war trauma antedated the outcome (personality pathology) before the observed association could be viewed as evidence for causation which emphasizes the importance of Hill’s temporality criterion [38].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In other words, it is possible that IPDE caseness observed in some participants in the study has emerged secondary to severe trauma. This would be consistent with the findings from a recent systematic review which suggested that a proportion of adults with no pre-trauma personality pathology appear to go on to develop significant personality problems following the exposure to severe trauma [16]. However, one would need to demonstrate that severe war trauma antedated the outcome (personality pathology) before the observed association could be viewed as evidence for causation which emphasizes the importance of Hill’s temporality criterion [38].…”
Section: Discussionsupporting
confidence: 81%
“…Numerous studies with war veterans and victims of torture have reported higher levels of personality pathology in people with PTSD whatever the cause [1115]. Whilst some people who had been exposed to war trauma had underlying pre-trauma personality related problems, findings from a recent systematic review of extant literature suggested that a proportion of adults with no pre-trauma personality pathology who are exposed to severe trauma appear to go on to develop significant personality problems [16]. Higher levels of exposure to traumatic events have been consistently associated with the increased risk of having a diagnosis of PTSD [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, compared to people without mental disorders, people with mental disorders had a tremendously increased risk of reporting psychosocial impairments and difficulties ( Munjiza et al, 2014 ; Jobst et al, 2015 ); however, a survey of psychiatric hospitals revealed that inpatients expected to increase their social contacts while attending sports and exercise sessions ( Brand et al, 2016 ). In line with this, Masten et al (2011) showed that neurophysiological responses to peer rejection appeared to be a biomarker for the onset of adolescents’ risk for depression.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the events of all episodes of each show can be considered to happen simultaneously among the total population of the series. Therefore, the authors argue that it is appropriate to analyse fictional depictions of psychological disorders using the methodological approach described above and comparing the prevalence rates within the Star Trek series with realworld prevalence rates found in the literature (World Health Organization 2003; Pearson et al 2006;Plassman et al 2007;Richardson et al 2010;Sar 2011;Munjiza et al 2014; National Institute of Mental Health 2016).…”
Section: Methods: Quantitative Analysis -Frequencies and Prevalence Rmentioning
confidence: 99%